2014
DOI: 10.7150/ijms.6961
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Right Ventricular Muscle Mass in Idiopathic Dilated Cardiomyopathy: Impact of Left Ventricular Muscle Mass and Pulmonary Hypertension

Abstract: Introduction: Although chronic pulmonary hypertension and right ventricular (RV) function carry important functional and prognostic implications in idiopathic dilated cardiomyopathy (IDC), little information on RV muscle mass (RVMM) and its determinants has been published.Methods: Our study comprised thirty-five consecutive patients with IDC, left ventricular (LV) ejection fraction <40% and NYHA class ≥2. Hemodynamic data and parameters on LV and RV geometry were derived from right heart catheterisation and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…However, should the PH-DCM continue, unfortunately, pulmonary endothelial dysfunction will occur, resulting in significant vasoconstriction and irreversible remodelling of the pulmonary vessels, which will lead to right ventricular stasis and hypertrophy, eventually resulting in tricuspid regurgitation (TR) and SM at the tricuspid area on auscultation. 10 As the right ventricle is much more sensitive to prolonged pressure overload, over time, the right heart can be irreversibly damaged, eventually resulting in heart failure. 14 Based on the pathological process of the development of DCM described above, it is suggested that SM at the apex and tricuspid area, which, respectively indicate the presence of MR and TR, are feasible factors for predicting PH probability in DCM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, should the PH-DCM continue, unfortunately, pulmonary endothelial dysfunction will occur, resulting in significant vasoconstriction and irreversible remodelling of the pulmonary vessels, which will lead to right ventricular stasis and hypertrophy, eventually resulting in tricuspid regurgitation (TR) and SM at the tricuspid area on auscultation. 10 As the right ventricle is much more sensitive to prolonged pressure overload, over time, the right heart can be irreversibly damaged, eventually resulting in heart failure. 14 Based on the pathological process of the development of DCM described above, it is suggested that SM at the apex and tricuspid area, which, respectively indicate the presence of MR and TR, are feasible factors for predicting PH probability in DCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although RHC is the gold standard for PH diagnosis, it is relatively complicated, expensive and invasive and is associated with a number of complications. 10 Consequently, Doppler echocardiography is recommended by the ESC/ERS Guidelines as a tool for the detailed assessment of right heart haemodynamics, as it is considered a non‐invasive and widely available diagnostic instrument for PH‐DCM patients. 11 However, Doppler echocardiography could be technically demanding and often involves a significant cost; thus, the prediction of PH appears to be an impossible mission in some community hospitals with poorer methods of examination.…”
Section: Introductionmentioning
confidence: 99%
“…However, should the PH-DCM continue, unfortunately, pulmonary endothelial dysfunction will occur, resulting in signi cant vasoconstriction and irreversible remodelling of the pulmonary vessels, which will lead to right ventricular stasis and hypertrophy, eventually resulting in tricuspid regurgitation (TR) and SM at the tricuspid area on auscultation [10]. As the right ventricle is much more sensitive to prolonged pressure overload, over time, the right heart can be irreversibly damaged, eventually resulting in heart failure [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although RHC is the gold standard for PH diagnosis, it is relatively complicated, expensive, and invasive and is associated with a number of complications [10]. Consequently, Doppler echocardiography is recommended by the ESC/ERS Guidelines as a tool for the detailed assessment of right heart haemodynamics, as it is considered a non-invasive and widely available diagnostic instrument for PH-DCM patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, right ventricular uncoupling to the demands of the pulmonary circulation leads to RV failure [10]. The previous study has suggested that an increase in RV mass in DCM not only associated with a consequence of the myopathic process itself but also burden of pulmonary artery pressure rise [11]. So the RV is the ultimate victim of these vascular processes [3].…”
Section: Introductionmentioning
confidence: 99%